(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
In light of the developments and intense competition that the world has witnessed, the need to search for a sustainable and continuous competitive advantage for economic units has emerged, as the economic units must not lose sight of their interest in the activities they perform to achieve that advantage, and it can be said that the goal of the research is to identify the theoretical dimensions of the green value chain represented by: (Green research and development, green design, green manufacturing, green marketing, green services) and the dimensions of the sustainable competitive advantage represented by (quality, creativity, innovation, cost, response to the customer), as well as identifying the nature of the relationship between the green value chain and sustainable competitive advantage. Relying on the inductive approach and by reviewing the accounting research and studies in this field, and in order to achieve the goal of the research, (45) questionnaires were distributed to a randomly selected sample of employees of Ur State Company, and the descriptive analytical method was adopted for the purpose of testing the research hypotheses and the statistical program for science SPSS with its measures (arithmetic mean, standard deviation, Spearman correlation coefficient) and after the results appear, hypothesis testing and interpretation of the problem For the research, a number of conclusions were reached, the most important of which are: The economic units that seek to achieve a sustainable competitive advantage must take the environmental aspect into consideration, starting from the process of providing resources to distributing products and delivering them to customers, and the research recommended the need to apply the principles of the green value chain in economic units As one of the modern basic pillars for achieving competition as well as raising the level of awareness of the environmental aspect and making it a work pattern on which the activities of economic units run.